THEATER SPACES AND THE CHALLENGES OF CULTURAL DECENTRALIZATION IN BELO HORIZONTE - Vitória, José Ricardo; Emmendoerfer, Magnus Luiz (Seven Editora, 2025)
The article analyzes the territorial distribution of theatrical venues in Belo Horizonte. The research adopts a qualitative, descriptive and exploratory approach, using secondary data on the city’s urban configuration and a survey applied to 64 identified theater spaces, 25 of which answered the questionnaire. The data was analyzed using the thematic categorical content analysis technique, resulting in ten analytical dimensions. The results show a concentration of cultural facilities in the Center-South region, responsible for 67% of the theatrical venues mapped, in contrast to the absence or scarcity of these facilities in the peripheral regions. This concentration implies inequalities in access to infrastructure, funding, visibility and cultural participation. The study shows that the centralization of theaters not only reflects historical patterns of exclusionary urbanization, but also limits the development of effectively decentralized public culture policies. It thus seeks to contribute to the debate on cultural equity in the urban space and reinforces the urgency of public policies that articulate territorial justice, inclusion and cultural diversity. DOI: https://doi.org/10.56238/sevened2025.021-074